PENGARUH KOHESIVITAS KELOMPOK KERJA TERHADAP PERILAKU INOVATIF PADA GENERASI Z - Pujiandrie, Kelvin; Fauzia, Nurul; Wijanarko, Adrian (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2024)
Generation Z is a generation group that is innovative and creative and has high work enthusiasm and tries to make a positive contribution where they work. Companies need to ensure a comfortable and supportive work atmosphere, especially in the cohesiveness of work groups to encourage generation Z to create new ideas through their innovative behavior. Cohesiveness in work groups will increasingly create a cohesive and solid group in achieving common goals with innovative behavior that will provide innovation and creativity in the company, especially in generation Z. This research examines the influence of work group cohesiveness on innovative behavior in generation Z, among 100 respondents . These results indicate that work group cohesiveness has a significant positive influence on innovative behavior in generation Z.